Epidemiology and analysis of potential risk factors of high‐risk human papillomavirus (HPV) in Shanghai China: A cross‐sectional one‐year study in non‐vaccinated women. Issue 2 (18th November 2021) - Niu, Jiaxin; Pan, Shuting; Wei, Yingting; Hong, Zubei; Gu, Liying; Di, Wen; Qiu, Lihua
Abstract: Data regarding human papillomavirus (HPV) prevalence, its associated risk factors, and women's knowledge about this disease before the HPV vaccine was approved are limited in Shanghai, China. Therefore, we investigated these questions among females in Shanghai and aimed to provide comprehensive data to guide HPV vaccination and present the biopsychosocial risk factors that impact high‐risk HPV infection, and evaluate the level of knowledge and awareness of this disease among women aged 21–65 years old. A total of 6619 (aged from 21 to 65) women from different communities volunteered to participate in the HPV screening and complete questionnaires from December 2016 to December 2017 in the Department of Obstetrics and Gynecology of nine hospitals in Shanghai. Data were analyzed using sample logistic regression to assess biopsychosocial risk factors that impact high‐risk HPV infection and knowledge of HPV infection. A total of 632 (9.5%) cases were positive for high‐risk HPV test, 22.6% of them were HPV 16/18 infection, 77.4% of them were non HPV 16/18 infection. 40 potential risk factors may be related to high‐risk HPV infection, and there were 19 factors' p value < 0.1 from single factor logistic analysis. Finally, multivariable regression revealed education level, type of vaginitis, history of hyperlipidemias, family history of cancer, number of pregnancies, number of sex partners were independent risk factors for high‐risk HPV infection ( p < 0.05). When stratified by education level, women who finished graduate school had significantly greater knowledge of cervical cancer, cervical screening, and the relationship between HPV and cervical cancer than other groups ( p < 0.05). The prevalence rate of high‐risk HPV was a little lower than other regions in China and other countries, which may be related to regions, races, living habits, and economy. A less reported finding is that the history of vaginitis and the history of hyperlipidemias in our study were related to HPV infection. The majority of the participants had poor knowledge regarding cervical cancer, cervical screening, and the relationship between HPV and cervical cancer. Hence, these results should be served as a wake‐up call for the government to increase knowledge and awareness via the media and doctors.